Decentralized Planning in the Sixth Scheduled Area of India: a Study of Meghalaya - Umdor, Sumarbin (2009)
In order to decentralise the planning process, Article 243ZD of the Constitution of India directs States to constitute District Planning Committees which are responsible for formulating draft district pans by consolidating the plans of the panchayats and municipal bodies. This provision of the Constitution however, does not cover certain parts of the country. The 73rd and 74th Constitutional Amendment Acts, which paved the way for the creation of theses tier panchayati raj institutions and municipal bodies are not applicable to States like Maghalaya which are listed in the Sixth Schedule of the Constitution. An alternate structure of local self-government, called the Autonomous District Councils, operates here. This paper examines the planning structure in Maghalaya and highlights the absence of decentralization of planning structure in the State.